Hubungan Kadar Pb dalam Darah dengan Kejadian Gangguan Fungsi Hati pada Pekerja Peleburan Timah Hitam di Kabupaten Tegal - Fidiyatun Fidiyatun; Onny Setiani; Suhartono Suhartono (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background : Lead (Pb) is a toxic material which easily accumulated in human organs and can cause health problems.Pb in the blood can cause damage to a variety of human organs including the liver. Results of preliminary studies inSmall Industry Village (PIK) Kebasen Tegal obtained that the air lead concentratios exceed the required standard,lead concentrations in the blood and parameters of liver function (AST, ALT and Gamma GT) on several workers wellbeyond normal limits.Methods : Cross-sectional study on 55 subjects research at Small Industry Village Kebasen Talang District Tegalregency. Pb levels in the blood as biomarker of Pb exposure on levels of ALT, AST and Gamma GT as a parameter formeasuring the physiology of Liver function. Data were collected through observation, interviews and laboratorytests. Univariate analysis, bivariate analysis by Chi-square, then followed by multivariate logistic regression.Result : Kendall Tau test showed significant association between blood lead level with the level of AST (p = 0.000),ALT (p = 0.025) and Gamma GT (0.001). Result of Chi-square test showed significant association between blood leadlevel with liver dysfunction (p = 0.002), prevalence ratio (PR) with 95% CI = 1.783 (1.360 to 2.337).Conclusion : There is a significant association between blood lead level and liver dysfunction on lead exposedworkers at small industries villages Kebasen district Tegal.Keywords : Lead exposure, AST, ALT, Gamma GT, Toxic Lead and Liver Function.